Behavior of varieties and hybrids of corn at two plant densities and two fertility levels - Sangoi, Luíz (Pesquisa Agropecuaria Brasileira, 2014)
This research was carried out in Lages, SC, Brazil, during 1985/86, 1986/87 and 1987/88 growing seasons, with the purpose of evaluate the yield and components of com varieties and hybrids at two planting populations and two fertility levels. The traits were disposed in a split-split piot design. The fertility levels tested were no fertilizer and 20,80 and 70 kg per hectare of N, P205, and K2O, respectively, at planting, plus 80kg of N as side-dressing. The cultivars were sowed at 25.000 and 50.000 plants/hectare. At 1985/86 growing season a low grain yield was observed due to water stress. In this year the fertility level and plant population did not affect grain yield. The better frequence and distribution of rains ar 1986/87 and 1987/88 growing seasons increased grain yield and fertility response of cultivars, specially at 50.000 plants/ha population. In these years hybrids presented higher grain yield than varieties at both fertility levels and plant population tested.